Artificial Light as a Modulator of Mosquito-Borne Disease Risk - Coetzee, Bernard W. T.; Gaston, Kevin J.; Koekemoer, Lizette L.; Kruger, Taneshka; Riddin, Megan A.; Smit, Izak P. J. (Frontiers in Ecology and Evolution, 2022)
Light is a fundamental cue regulating a host of biological responses. The artificial modification thereof demonstrably impacts a wide range of organisms. The use of artificial light is changing in type, extent and intensity. Insect vector-borne diseases remain a global scourge, but surprisingly few studies have directly investigated the interactions between artificial light and disease vectors, such as mosquitoes. Here we briefly overview the progress to date, which highlights that artificial light must be considered as a modulator of mosquito-borne disease risk. We present a framework showing where the mechanisms may lie, and where future research could usefully be directed, particularly in advancing understanding of the biological effects of the light environment. Further understanding of how artificial light may modulate mosquito-borne disease risk may assist in employing and redesigning light regimes that do not increase, and may even mitigate, already significant disease burdens, especially in the developing world.